Why is it important to implement meta-research in universities and institutes with medical research activities? - Lozada-Martinez, Ivan David; Neira-Rodado, Dionicio; Martinez-Guevara, Darly; Cruz-Soto, Hary Salome; Sanchez-Echeverry, Maria Paula; Liscano, Yamil (Frontiers in Research Metrics and Analytics, 2025)
In recent years, there has been a growing concern over questionable practices and a lack of rigor in scientific activities, particularly in health and medical sciences. Universities and research institutes are key players in the development of science, technology, and innovation. Academic institutions, whose primary mission is to generate and disseminate knowledge, bear the responsibility in many parts of the world to act as consultants and guardians of scientific integrity in health research. Then, universities and research institutes must act as guardians of the research and technological development process, utilizing methodological and operational evaluation tools to validate the rigor and quality of medical research. Meta-research is defined as the research of research itself. Some of the most important specific objectives of meta-research include the assessment of research relevance, the evaluation of evidence validity, and the exploration of scientific integrity. A significant portion of evidence in the medical and health sciences literature has been found to be redundant, misleading, or inconsistent. Although this issue is of great importance in global health, discussions about practical and tangible solutions remain fragmented and limited. The aim of this manuscript is to highlight the significance of employing meta-research within universities and research institutes as a tool to monitor scientific rigor and promote responsible practices in medical research.